(untitled) (Dimensión Empresarial, 2019)
This paper presents theoretical reflections whose purpose is to discuss the performance of Multinational Enterprises (MNEs) and the fact that the impacts of their activities are the result of their management, despite their focus on Corporate Social Responsibility (CSR). For this purpose, we reviewed some of the main CSR concepts and reference documents to identify in which way this type of organization could be contributing to global inequality. Additionally, we describe the characteristics of the general orientation of CSR in these companies. The main results indicate that when moving to less developed countries, MNEs take advantage of the existing unequal conditions of income and precariousness of labor and environmental rules. The construction of a favorable image through CSR contributes to MNEs success, but at the cost of a complex and intense process of concentration of wealth and deepening of social inequality and poverty.